2017
DOI: 10.1007/s00436-017-5407-0
|View full text |Cite
|
Sign up to set email alerts
|

First record of three African trichodinids (Ciliophora: Peritrichida) in cultured Nile tilapia (Oreochromis niloticus) in Saudi Arabia with re-evaluation of their host specificity

Abstract: Saudi Arabia has a developing aquaculture industry that farms primarily tilapia. Although trichodinids are presumably the most usually encountered protozoan parasites in these cultured fish, they have rarely been studied in this context, and there is no data on the species that might infect cultured tilapia in Saudi Arabia. The present study was therefore carried out as a general survey to investigate the occurrence and identify the species of trichodinids that can infect cultured tilapia (Oreochromis niloticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Subsequently, T. maritinkae was described from two other South African Clarias species and from another Clarias species in Taiwan and China, thus the host specificity for Clarias species has been assumed (Basson & Van As, ; Van As & Basson, ). However, succeeding studies, including this study, have contradicted this opinion and indicated that T. maritinkae shows low host specificity (Abdel‐Baki et al, ; Yu, Zhao, & Tang, ). The population described in this study possessed shorter rays and fewer radial pins than those of the previously reported populations.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Subsequently, T. maritinkae was described from two other South African Clarias species and from another Clarias species in Taiwan and China, thus the host specificity for Clarias species has been assumed (Basson & Van As, ; Van As & Basson, ). However, succeeding studies, including this study, have contradicted this opinion and indicated that T. maritinkae shows low host specificity (Abdel‐Baki et al, ; Yu, Zhao, & Tang, ). The population described in this study possessed shorter rays and fewer radial pins than those of the previously reported populations.…”
Section: Resultsmentioning
confidence: 61%
“…Trichodina species have long been considered a primary cause of disease outbreaks in cultured fish (Abdel‐Baki et al, ; Maciel, Garcia, Chagas, Fujimoto, & Tavares‐Dias, ; Saha, Bandyopadhyay, & Göçmen, ; Tang, Zhang, & Zhao, ; Valladao, Gallani, Padua, Martins, & Pilarski, ; Wang, Zhou, Guo, et al, ). Basson and Van As () pointed out that the larval and juvenile stages of fish are the most susceptible to Trichodina infestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these, the trichodinids are among the most commonly encountered; in the tilapia culture industry (Abdel‐Baki et al . , 2017), their infection pressure is linked to high levels of organic matter in the water (Madsen et al . , 2000).…”
Section: Introductionmentioning
confidence: 99%